Analisis Nilai Moral Perjuangan Ibu dan Anak dalam Film Mars: Kajian Sosiologi Sastra - Pitriani, Pipit; Alsunah, Aditya Ansor; Nurwahidah, Lina Siti; Julianto, Cecep Dudung (Asosiasi Ide Bahasa Kepri, 2025)
Literary works are a depiction of the imaginary life of a writer. One form of literary work is film. This study aims to describe the moral values ​​in the film entitled MARS